Resolver a expressão:
0,3+(2/3-1/4)-(-7/12+4/3)=
Resolver as equações em R:
a) 3 (2x - 3) + 2 (x + 1) = 3x +8
b) 2x +3 (x - 4) = 4x + 9
Soluções para a tarefa
Respondido por
1
1) ![0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}{12}+\dfrac{4}{3}\right) 0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}{12}+\dfrac{4}{3}\right)](https://tex.z-dn.net/?f=0%2C3%2B%5Cleft%28%5Cdfrac%7B2%7D%7B3%7D-%5Cdfrac%7B1%7D%7B4%7D%5Cright%29-%5Cleft%28-%5Cdfrac%7B7%7D%7B12%7D%2B%5Cdfrac%7B4%7D%7B3%7D%5Cright%29)
Note que:
![\dfrac{2}{3}-\dfrac{1}{4}=\dfrac{8-3}{12}=\dfrac{5}{12} \dfrac{2}{3}-\dfrac{1}{4}=\dfrac{8-3}{12}=\dfrac{5}{12}](https://tex.z-dn.net/?f=%5Cdfrac%7B2%7D%7B3%7D-%5Cdfrac%7B1%7D%7B4%7D%3D%5Cdfrac%7B8-3%7D%7B12%7D%3D%5Cdfrac%7B5%7D%7B12%7D)
![\dfrac{-7}{12}+\dfrac{4}{3}=\dfrac{-7+16}{12}=\dfrac{9}{12} \dfrac{-7}{12}+\dfrac{4}{3}=\dfrac{-7+16}{12}=\dfrac{9}{12}](https://tex.z-dn.net/?f=%5Cdfrac%7B-7%7D%7B12%7D%2B%5Cdfrac%7B4%7D%7B3%7D%3D%5Cdfrac%7B-7%2B16%7D%7B12%7D%3D%5Cdfrac%7B9%7D%7B12%7D)
Então:
![0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}{12}+\dfrac{4}{3}\right)=0,3+\dfrac{5}{12}-\dfrac{9}{12} 0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}{12}+\dfrac{4}{3}\right)=0,3+\dfrac{5}{12}-\dfrac{9}{12}](https://tex.z-dn.net/?f=0%2C3%2B%5Cleft%28%5Cdfrac%7B2%7D%7B3%7D-%5Cdfrac%7B1%7D%7B4%7D%5Cright%29-%5Cleft%28-%5Cdfrac%7B7%7D%7B12%7D%2B%5Cdfrac%7B4%7D%7B3%7D%5Cright%29%3D0%2C3%2B%5Cdfrac%7B5%7D%7B12%7D-%5Cdfrac%7B9%7D%7B12%7D)
Mas,![0,3=\dfrac{3}{10}=\dfrac{3\cdot1,2}{10\cdot1,2}=\dfrac{3,6}{12} 0,3=\dfrac{3}{10}=\dfrac{3\cdot1,2}{10\cdot1,2}=\dfrac{3,6}{12}](https://tex.z-dn.net/?f=0%2C3%3D%5Cdfrac%7B3%7D%7B10%7D%3D%5Cdfrac%7B3%5Ccdot1%2C2%7D%7B10%5Ccdot1%2C2%7D%3D%5Cdfrac%7B3%2C6%7D%7B12%7D)
Assim:
![0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}12}+\dfrac{4}{3}\right)=\dfrac{3,6}{12}+\dfrac{5}{12}-\dfrac{9}{12}=\dfrac{3,6+5-9}{12}=\dfrac{-0,4}{12} 0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}12}+\dfrac{4}{3}\right)=\dfrac{3,6}{12}+\dfrac{5}{12}-\dfrac{9}{12}=\dfrac{3,6+5-9}{12}=\dfrac{-0,4}{12}](https://tex.z-dn.net/?f=0%2C3%2B%5Cleft%28%5Cdfrac%7B2%7D%7B3%7D-%5Cdfrac%7B1%7D%7B4%7D%5Cright%29-%5Cleft%28-%5Cdfrac%7B7%7D12%7D%2B%5Cdfrac%7B4%7D%7B3%7D%5Cright%29%3D%5Cdfrac%7B3%2C6%7D%7B12%7D%2B%5Cdfrac%7B5%7D%7B12%7D-%5Cdfrac%7B9%7D%7B12%7D%3D%5Cdfrac%7B3%2C6%2B5-9%7D%7B12%7D%3D%5Cdfrac%7B-0%2C4%7D%7B12%7D)
Veja que,
. Deste modo:
![0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}{12}+\dfrac{4}{3}\right)=\dfrac{\frac{-2}{5}}{12}=\dfrac{-2}{5}\cdot\dfrac{1}{12}=\dfrac{-2}{60}=\dfrac{-1}{30} 0,3+\left(\dfrac{2}{3}-\dfrac{1}{4}\right)-\left(-\dfrac{7}{12}+\dfrac{4}{3}\right)=\dfrac{\frac{-2}{5}}{12}=\dfrac{-2}{5}\cdot\dfrac{1}{12}=\dfrac{-2}{60}=\dfrac{-1}{30}](https://tex.z-dn.net/?f=0%2C3%2B%5Cleft%28%5Cdfrac%7B2%7D%7B3%7D-%5Cdfrac%7B1%7D%7B4%7D%5Cright%29-%5Cleft%28-%5Cdfrac%7B7%7D%7B12%7D%2B%5Cdfrac%7B4%7D%7B3%7D%5Cright%29%3D%5Cdfrac%7B%5Cfrac%7B-2%7D%7B5%7D%7D%7B12%7D%3D%5Cdfrac%7B-2%7D%7B5%7D%5Ccdot%5Cdfrac%7B1%7D%7B12%7D%3D%5Cdfrac%7B-2%7D%7B60%7D%3D%5Cdfrac%7B-1%7D%7B30%7D)
a)![3(2x-3)+2(x+1)=3x+8 3(2x-3)+2(x+1)=3x+8](https://tex.z-dn.net/?f=3%282x-3%29%2B2%28x%2B1%29%3D3x%2B8)
![6x-9+2x+2=3x+8 6x-9+2x+2=3x+8](https://tex.z-dn.net/?f=6x-9%2B2x%2B2%3D3x%2B8)
![8x-3x=8+7 8x-3x=8+7](https://tex.z-dn.net/?f=8x-3x%3D8%2B7)
![5x=15 5x=15](https://tex.z-dn.net/?f=5x%3D15)
![x=3 x=3](https://tex.z-dn.net/?f=x%3D3)
b)![2x+3(x-4)=4x+9 2x+3(x-4)=4x+9](https://tex.z-dn.net/?f=2x%2B3%28x-4%29%3D4x%2B9)
![2x+3x-12=4x+9 2x+3x-12=4x+9](https://tex.z-dn.net/?f=2x%2B3x-12%3D4x%2B9)
![5x-4x=12+9 5x-4x=12+9](https://tex.z-dn.net/?f=5x-4x%3D12%2B9)
![x=21 x=21](https://tex.z-dn.net/?f=x%3D21)
Note que:
Então:
Mas,
Assim:
Veja que,
a)
b)
Perguntas interessantes
Inglês,
1 ano atrás
Português,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás
Química,
1 ano atrás